Design and validation of the scale for the adoption of artificial intelligence in the online shopping experience of Peruvian consumers - Cruz-Tarrillo, José Joel; Tarrillo-Paredes, Jose; Haro-Zea, Karla Liliana; Díaz Saavedra, Robin Alexander Díaz (Frontiers in Artificial Intelligence, 2026)
Artificial intelligence has become a crucial tool for effective customer management; therefore, this research aims to design and validate a scale measuring the adoption of artificial intelligence in the customer experience. It is approached from a quantitative methodology perspective and an instrumental design. A survey was conducted among 528 customers who frequently make virtual purchases. Then, an exploratory analysis was conducted to determine the factor structure of the scale, followed by a confirmatory analysis to validate the construct. On the other hand, an invariance analysis was conducted to determine whether the construct varies across groups. The results show a multidimensional scale of 16 items grouped into 4 factors (trust in AI, perception of AI, knowledge of AI, shopping experience). Each factor consists of four items, using a Likert-type response scale where 1 indicates “totally disagree” and 5 indicates “totally agree”. In conclusion, the proposed scale is a valid measure. It can be used to continue exploring this concept in other latitudes, serving as a valuable tool for entrepreneurs to make an effective diagnosis of this new technology.